Lipid Signaling in T Cell Development and Function - Karsten Sauer (Frontiers Research Topics, 2015)
Lipids are best known as energy storing molecules and core-components of cellular membranes, but can also act as mediators of cellular signaling. This is most prominently illustrated by the paramount importance of the phospholipase C (PLC) and phosphoinositide 3-kinase (PI3K) signaling pathways in many cells, including T cells and cancer cells. Both of these enzymes use the lipid phosphatidylinositol(4,5)bisphosphate (PIP2) as their substrate. PLCs produce the lipid product diacylglycerol (DAG) and soluble inositol(1,4,5)trisphosphate (IP3). DAG acts as a membrane tether for protein kinase C and RasGRP proteins. IP3 is released into the cytosol and controls calcium release from internal stores. The PI3K lipid product phosphatidylinositol(3,4,5)trisphosphate (PIP3) controls signaling by binding and recruiting effector proteins such as Akt and Itk to cellular membranes. Recent research has unveiled important signaling roles for many additional phosphoinositides and other lipids. The articles in this volume highlight how multiple different lipids govern T cell development and function through diverse mechanisms and effectors. In T cells, lipids can orchestrate signaling by organizing membrane topology in rafts or microdomains, direct protein function through covalent lipid-modification or non-covalent lipid binding, act as intracellular or extracellular messenger molecules, or govern T cell function at the level of metabolic regulation. The cellular activity of certain lipid messengers is moreover controlled by soluble counterparts, exemplified by symmetric PIP3/inositol(1,3,4,5)tetrakisphosphate (IP4) signaling in developing T cells. Not surprisingly, lipid producing and metabolizing enzymes have gained attention as potential therapeutic targets for immune disorders, leukemias and lymphomas.